Analisis Produksi Alat Gali Muat dan Alat Angkut pada Pemindahan Overburden Penambangan Batubara PT Duta Tambang Rekayasa di Kabupaten Nunukan, Provinsi Kalimantan Utara - Adam Sutodrono; Zaenal; Sriyanti (Bandung Conference Series: Mining Engineering, 2023)
Abstract. The research method used is to make measurements first, such as available time, productive time, inhibition time, circulation time, bucket capacity, material weight, material volume. The measurement of cycle time is aimed at digging and loading equipment and conveyance pairs in one mining cycle. The data processing carried out is looking for production and efforts to increase production on overburden removal. Environmental conditions in the 2017-2021 timeframe have an average rainfall of 219.25 mm/year. The efficiency of the loading and digging equipment is 77.92%, while for the transportation equipment it is 80.40%. The circulation time obtained for the digging equipment is 26.87 seconds or 0.45 minutes, and for the transportation equipment it is 5.47 minutes. The Swell Factor obtained was 79.86%, and the Fill Factor was 85.05%. Production results of loading and unloading equipment amounted to 473,20 tons/hour, and transportation equipment amounted to 473,98 tons/hour. The compatibility value of the tool is 0.97. The production target was 558.60 tons/hour. From this target, the production of loading and hauling equipment had not been achieved, then the compiler made efforts to improve production. Abstrak. Metode penelitian yang dilakukan adalah melakukan pengukuran terlebih dahulu, seperti waktu tersedia, waktu produktif, waktu hambatan, waktu edar, kapasitas bucket, berat material, volume material. Pengukuran waktu edar ditujukan pada alat gali-muat serta pasangan alat angkut dalam satu siklus penambangan. Pengolahan data yang dilakukan adalah mencari produksi dan upaya peningkaan produksi pada pemindahan overburden. Kondisi lingkungan dalam rentang waktu 2017-2021 memiliki curah hujan rata-rata 219,25 mm/tahun. Efisiensi alat gali muat sebesar 77,95 %, sedangkan untuk alat angkut senilai 80,45 %. Waktu edar yang didapatkan pada alat gali muat sebesar 26,87 detik atau 0,45 menit, serta untuk alat angkut sebesar 5,47 menit. Swell Factor yang didapatkan sebesar 79,88 %, dan Fill Factor sebesar 85,05 %. Hasil Produksi alat gali muat sebesar 473,20 ton/jam, serta alat angkut sebesar 473,98 ton/jam. Nilai keserasian alat adalah 0,97. Target produksi adalah 558,60 ton/jam dari target tersebut produksi alat gali muat dan angkut belum tercapai, kemudian penyusun melakukan upaya perbaikan produksi.